Promotion of ecological safety in Warsaw-Bielany - Grunt-Mejer, Iwona (Studia Ecologiae et Bioethicae, 2003)
That paper shows the most important thesis of the author’s dissertation. The dissertation mainly realizes diagnostic aims. The problem takes up in it concerns the real role of local government in ecological safety promotion. The basis point of reference is the typology of instruments and styles of realization social policy. Ecological safety is one of the more important needs of humans. On the other hand, the local government in the typology of entity realizing social policy is located as a public and legal entity, which acts on a local scale. The adoption method of study case has been a way to realize cognitive aim and grant research appliqué value, comparison base for different local governments. The dissertation has theoretical value, too (there is indirectly check the accuracy of safety promotion definition during research). The statement, that local government ought to and able to be a teacher in ecological safety matters can be considered as basis conclusions.